The relationship between fermentable carbohydrates and post-prandial bowel symptoms in patients with functional bowel disorders - MacIntosh, Alice; Heenan, Phoebe E.; Wright-McNaughton, Morag; Frampton, Chris; Skidmore, Paula; Wall, Catherine L.; Muir, Jane; Talley, Nicholas Joseph; Roy, Nicole Clemence; Gearry, Richard B. (Frontiers in Nutrition, 2023)
Background and aims A low fermentable oligosaccharide, disaccharide, monosaccharide, and polyols (FODMAP) diet alleviates symptoms of irritable bowel syndrome (IBS). We aimed to investigate the relationship between habitual FODMAP intake and post-prandial bowel symptoms in adults with IBS, functional diarrhoea (FD), or constipation (FD) (functional bowel disorders), and in healthy adults (controls). Methods 292 participants (173 with functional bowel disorders and 119 controls) completed a food and symptom times diary. Estimated meal portion sizes were entered into the Monash FODMAP Calculator to analyse FODMAP content. Wilcoxon and ANOVA tests were used to investigate the relationship between FODMAP intake and post-prandial bowel symptoms. Results IBS participants experienced more post-prandial bowel symptoms compared to participants with other functional bowel disorders or controls. Meals associated with abdominal pain contained on average increased excess fructose (0.31 g vs. 0.18 g, p < 0.05), sorbitol (0.27 g vs. 0.10 g, p < 0.01), and total FODMAP (3.46 g vs. 2.96 g, p < 0.05) compared to meals not associated with pain. Abdominal swelling was associated with increased sorbitol (0.33 g vs. 0.11 g, p < 0.01), and total FODMAP (3.26 g vs. 3.02 g, p < 0.05) consumption. Abdominal bloating was associated with increased galacto oligosaccharide consumption (0.18 g vs. 0.14 g, p < 0.05). Conclusion These findings support the role of FODMAP in post-prandial bowel symptom onset, however, the amount and type of FODMAP triggering symptoms vary between individuals. Future research should investigate the relationship between the effect of individual FODMAP consumption on post-prandial bowel symptoms for each subtype, the interaction of FODMAP with differing functional bowel disorders and whether longitudinally symptoms and dietary intake are stable.